A conversa, a escuta e as cartas como modo de pesquisa-VIDA-formação: matizes para uma educação na/da diferença junto a professoras de crianças com autismo - Rocha, Simone de Paula (2025)
This is a research entangled by ConversActions others in the/of with the school routine. I choose colors for the paletteresearch with shades of listening and of talking, with a political epistemological choice which prioritizes life in its multiples versions and helps us to not forget that we are humans. In this process of narrating life, I bring to the conversationresearch the metaphor with the ribbon colors that compose the symbol of autism, in a perspective other of dialoguing with a theme, since this composition arises from my own life story of mother of a child with Autism Spectrum Disorder -ASD and teacher of the Specialized Educational Assistance -AEE. The nuances of the research are constituted from the proposal of an extension course for the teachers that act in the AEE, in a movement woven in the/of and through research-LIFE-education and it is linked to the Federal University of São Carlos and the Regional Board of Education - DRE of the Rondonópolis-MT Pole. The study proposes to biographize the experiences that compose the teaching work of the teachers in the assistance to children with ASD. I choose as methodological device the Pedagogical Letters and establish as objective comprehending, from the narratives the way in which the teaching knowledges are (re)known, (re)dimensioned and constitute the assistance of the ASD students, in the state network of the Rondonópolis-MT Pole and in Pole 16 of the State of São Paulo. The thesis is organized in Mailboxes with Pedagogical Letters parting from the colors which compose the ribbon symbol of autism. Each Mailbox brings the weaving of the movement of research in/of/with the school routine and tone meaningful reflections in the field of Special Education. In the inset of the colors and shades of the writingresearch I find in Josso the tone of the life stories. With Passeggi and Souza the nuances that sustain the research in the (Auto)biographical approach. In Freire the in-between tones in the dialogicity. Freitas, arrives and composes the palette with the device of the Pedagogical Letters. Skliar, brings the nuances of listening and of talking. I defend that biographize the voices that echo the school routines is sheltering a timespace other, in a logic which embraces the listening of the senses, a sensitive listening, in a journey that begins with the listening of our own and the conscience of the (co)existence. A movement of learningteaching of how we see, feel and think in the/of difference. The research enunciates a perspective of self-education and Converseducation from the experiential knowledges inhabited in the centrality of the pedagogical constructions and, announces a convers(action) in a horizontal movement of conversation, listening and writing which is done in the art of the encounter between the pauses of time and the time necessary for the pauses.